EPCR Gene Ser219Gly Polymorphism and Venous Thromboembolism: A Meta-Analysis of 9,494 Subjects - Li, Yan-yan; Wu, Jing-jing; Yang, Xin-xing; Geng, Hong-yu; Gong, Ge; Kim, Hyun Jun (Frontiers in physiology, 2017)
Although gene Ser219Gly polymorphism has been associated with venous thromboembolism (VTE) susceptibility, no clear consensus has yet been reached. A meta-analysis of 9,494 subjects from 13 individual studies was conducted to better elucidate the potential relationship between the gene Ser219Gly polymorphism and VTE. Pooled odds ratios (ORs) and their corresponding 95% confidence intervals (CIs) were evaluated by using fixed or random effect models. The current meta-analysis suggested that there was a significant association between gene Ser219Gly polymorphism and VTE under allelic (OR: 1.42, 95% CI: 1.21-1.66, = 1.30 × 10 ), recessive (OR: 2.02, 95% CI: 1.44-2.85, = 5.35 × 10 ), homozygous (OR: 2.24, 95% CI: 1.59-3.16, = 3.66 × 10 ), and additive genetic models (OR: 1.63, 95% CI: 1.30-2.04, = 2.24 × 10 ). gene Ser219Gly polymorphism was associated with an elevated risk of VTE and the Gly residue carriers of the gene might be predisposed to VTE.